Global Cardiovascular Risk Assessment by Family Physicians in Suez Canal University-Family Medicine Centers-Egypt - Nour-Eldein, Hebatallah (J Family Med Prim Care, 2013)
BACKGROUND: The close sustained contact of family physician with their patients and local community makes preventive care an integral part of their routine work. Most cardiovascular diseases (CVD) can be prevented by addressing their risk factors. There are several guidelines that recommend different CV risk assessment tools to support CV prevention strategies. AIM: This study aimed to assess awareness and attitude of global CV risk assessment and use of their tools by family physicians; aiming to improve CV prevention service. METHODS: The current study is a cross-sectional descriptive analytic. Sixty-five family physicians were asked to respond to, validated anonymous questionnaire to collect data about characteristics of family physicians, their awareness, attitude, current use, barriers, and recommendations of global CV risk assessment. Statistical Package for Social Sciences (SPSS) version 18 was used for data entry and analysis. RESULTS: Awareness of guidelines of global CV risk assessment was relatively higher regarding the American guidelines (30.8%) than that recommended by World Health Organization (WHO) for Egypt (20.2%). 50.8% of participants had favorable attitude. There was statistical significant relationship between attitude scores and physician characteristics; age (P = 0.003), qualification (P = 0.001) and number of patients seen per week (P = 0.009). Routine use of global CV risk assessment tools was reported only (23%) by family physicians. CONCLUSION: Relative higher attitude scores than use of global CV risk assessment tools in practice. The most frequent barriers were related to lack of resources and shortage in training/skills and the raised suggestions were towards training.